Instructional Design for the Teaching of Reading Skill to the Eight Grade Students of SMP Muhammadiyah 7 Surakarta: A Naturalistic Study in 2015/2016 Academic Year - Solikah, Listiyo Wakidatu; , Prof. Dr. Endang Fauziati, M. Hum; , Siti Fatimah, S. Pd, M. Hum (2016)
The study is aimed at observing the instructional design for teaching reading at SMP Muhammadiyah 7 Surakarta. It is conducted to know the instructional design for the teaching reading at eight grade students in SMP muhammadiyah 7 Surakarta. The researcher gets the data from event, informant and document. The technique of collecting data in this research are observation in teaching reading process and interview the teacher about the instructional design of teaching reading. The result of this research shows that instructional design is as follows: 1) learning objectives of teaching reading is divided into two. The general learning objective is based on syllabus and the specific learning objective is based on lesson plan for the eight grade. 2) Classroom procedure used by the teacher is divided into three steps namely Exploration, Elaboration and Confirmation in teaching learning process which the classroom activities are included in them. 3) The teacher used some techniques in the teaching learning process such as question and answer, reading aloud, translation, silent reading, giving feedback and summarizing. 4) The material used by English teacher was generally taken from some sources. The teacher used textbook as printed material and unprinted materials from slide of power point which made before teaching in the class and took from the internet or other resources. 5) The English teacher has complete role in the teaching learning activities. Teacher's role in teaching English are as facilitator, manager, monitor and evaluator. 6) The student's role of teaching reading in SMP Muhammadiyah 7 Surakarta was as listener and performer.